Mais do que "levantar, sacudir a poeira e dar a volta por cima": um estudo sobre a autonomia superativa e emancipatória de mulheres negras cariocas - Carvalho, Liandra Lima (2008)
This study aimed to examine the trajectory of black women Cariocas, as was done for a critical reassessment of the concepts: resilience and empowerment, that were show a new field about autonomy and emancipatory . As well as, a discussion based on an analysis in history and social indicators, seeking discuss about "social place" occupied by Brazilian black women, contemplating since their arrivals, coming from Africa to this day. For reasons of this work has been carried out a qualitative social research, where they were interviewed five black women, entered into various segments professionals, residents in different localities of the State of Rio de Janeiro.